Degenerative rotator cuff tear in an elderly athlete: a case report - Kazemi, Mohsen (1999)
The incidence of rotator cuff tear increases with age. Degenerative rotator cuff tears are commonly seen in athletes above 40 years. These athletes are commonly involved in overhead activities. Repetitive microtrauma is a more important factor in rotator cuff degeneration than acute trauma. Conservative treatment is the mainstay treatment for these injuries. A case report of an elderly athlete who sailed competitively is presented. The clinical and radiographic presentations, management and rehabilitation of degenerative rotator cuff tears are discussed.